The Need of Journals as a Publication Platform in The Field of Special Nutrition in Indonesia - Basrowi, Ray Wagiu (Journal of Indonesian Specialized Nutrition, 2023)
The field of specialized nutrition plays an important role in improving people's health and quality of life. Indonesia has various nutritional problems that need to be addressed, including malnutrition, overnutrition, and other nutritional disorders. The need for journals as a publication platform in the field of specialty nutrition in Indonesia is very important. The purpose of this study was to assess the need for journals as a publication platform in the field of specialty nutrition in Indonesia. This research uses a qualitative method with a case study approach. The object of this research is the journal of Indonesian specialized nutrition (JISN). Data collection techniques in this study used literature study and interviews. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that JISN facilitates authors, academics, students, and health professionals to share their scientific work in the field of community and clinical nutrition, as well as other related fields including epidemiology, community nutrition, family medicine, health economics, and other public health research. The journal is also a platform to provide learning and recommendations in the field of specialty nutrition and related data for the development of good health practices for the people of Indonesia and the world. These needs are the basis for journal managers to improve the quality and reach of journals in the field of specialty nutrition in Indonesia.